Historyczne aspekty semantyki celownika - Brandner, Aleš (Przegląd Rusycystyczny, 2006)
HISTORYCZNE ASPEKTY SEMANtYKI CELOWNIKA Streszczenie W artykule przedstawiono historię użycia form celownika, która pozwala hipotetycznie odtworzyć kształtowanie się jego semantyki. Szczególną uwagę zwrócono uwagę na jego najstarsze znaczenie — przestrzenne. Autor konstatuje, że w wyniku utraty znaczenia przestrzennego, przypadek ten we współczesnym języku rosyjskim funkcjonuje jako:— celownik z pozostałościami dawnego użycia przestrzennego (obiekt „myślowego dotknię-cia”);— celownik z ogólnym znaczeniem adresata;— celownik jako konstrukcja zdania prostego z ogólnym znaczeniem agensa.Oprócz rysu historycznego, przytoczono przykłady znaczeń form celownika we współczesnym języku rosyjskim, które tworzą barwny i jednocześnie zagmatwany obraz tego przypadka. HISTORICAL SEMANTIC FEATURES OF THE DATIVE IN RUSSIAN Summary Semantic meaning, which is expressed in contemporary Russian by means of dative constructions, represents a very varied and complex subject. Historical study of the dative form’s use enables us to hypothesise their original semantics.In old Russian, the connection between words and their syntectical placement in a sentence was different in comparison with the situation in present day language. Particularly noticeable are differences in syntactical constructions such as (verbal) governance. the nominative form’s role in a sentence is the function of the subject and nominal predicate. Indirect cases most often express the object and less often the adverbial, and with the noun, function as an attribute. thus indirect cases determined by a verb, and indirect cases which are dependant on a noun, adjective and numeral, are distinguished. throughout the historical development of Russian there were essential changes in the system of (verbal) governance and the meanings of some of the simple and prepositional cases have changed. these changes have come about due to a general tendency of the language to become more specific by attempting to express the exact meaning. the scope of relationships expressed by simple cases, cases without prepositions , and non-prepositional cases decreased. Non-prepositional cases were replaced by constructions with various prepositions. At the same time the semantics of each preposition were reduced, mainly their polysemy, which was the cause of many a misinterpretation in expression. Specific examples of general statements are given in the article.